Characterization of antidiabetic and antioxidant activity of Brucea javanica (L.) Merr. Seeds / Abdulwali Ablat - Abdulwali , Ablat (2018)
Brucea javanica (L.) Merr is a medicinal plant used for hyperlipidemia and diabetes in Malay traditional medicine. This study was designed to evaluate antidiabetic and antioxidant effects of Brucea javanica seed (BJS) in vitro and in vivo and also identify chemical compounds that could be responsible for its pharmacological activity. The results showed that the ethyl acetate fraction (EAF) was identified as a most active GPα inhibitor with IC50 = 0.75 mg/ml. The EAF effectively scavenged DPPH, NO and superoxide radicals and it reduced ferric ion to ferrous, but failed to trap this ion compared with other fractions in antioxidant assays. In animal study, the EAF exhibited antihyperglycemic effect without causing weight gain and showed strong hypolipidimic effect in diabetic rats. The EAF treatment to diabetic rats also significantly increased insulin level, markedly improved glycogen metabolism and glucose tolerance which validated its use as an antidiabetic agent in traditional medicine. It also enhanced antioxidant defense by suppressing oxidative stress and exerted anti-inflammatory effect by decreasing serum TNF α, IL-6 and IL-1β in diabetic rats compared with controls. Chromatographic separation of the EAF led to the isolation of seven known compounds; vanillic acid, bruceine D, bruceine E, parahydroxybenzoic acid, luteolin, protocatechuic acid and gallic acid. The GPα and α-glucosidase inhibition assays resulted in identification of luteolin as the most effective compound in BJS with the IC50 values of 45.1 and 26.4 μM. While vanillic acid, bruceine D and bruceine E were inactive, other compounds parahydroxybenzoic acid, protocatechuic acid and gallic acid showed weak inhibition of GPα (IC50 = 357.9, 297.4 and 214.4 μM) and α-glucosidase (IC50 = 649.1, 368.7 and 277.0 μM). Overall, the EAF reduced glycemia of T2D rats through diverse mechanisms acting as GPα and α-glucosidase inhibitors and luteolin most probably is the major contributor to the observed antidiabetic effects.